Comparing the efficacy of Chlorhexidine Mouthwash and Natural Honey in Reducing Plaque and Improving Gingival Health. A Randomized Controlled Trial: Plaque Reduction and Gingival Health - Abid, Muhammad; Baig, Muhammad Ilyas; Khurshid, Ambreen; Kumar, Ajet; Farooq, Sidra; Iqbal, Zafar (Pakistan Journal of Health Sciences, 2024)
Plaque control is essential for maintaining gingival health, if left untreated can lead to conditions like gingivitis and progress to periodontitis. Natural honey has been historically utilized for its antibacterial properties, while Chlorhexidine (CHX) is used as synthetic antimicrobial agent in oral care. Objective: The objective was to assess and compare the effectiveness of natural honey-based mouthwash and chlorhexidine in preventing dental plaque formation and improving gingival health. Methods: An open-label, randomized controlled trial was conducted with 60 participants aged 18 to 25. The study compared the effects of natural honey and chlorhexidine mouthwashes on dental plaque levels, employing the Silness and Loe index for plaque assessment. Participants were randomly assigned to either Group A (Chlorhexidine Mouthwash) or Group B (Natural Honey Mouthwash). Both groups followed a prescribed oral hygiene regimen, and plaque levels were measured at baseline and after two weeks. Results: Demographic characteristics of both groups were documented, including age, gender distribution, and level of education. Plaque and gingival indices were measured at baseline and after 21 days. Both groups showed a significant decrease in plaque and gingival indices after 21 days (p=<0.001). The honey mouthwash demonstrated a more pronounced reduction in the plaque (p=<0.001) and ginigival index (p=0.001) on Day 21, with a notable and statistically significant difference between the two groups. Conclusions: The study concludes that both natural honey and chlorhexidine mouthwashes effectively reduce plaque and improve gingival health. However, honey mouthwash exhibits superior efficacy, suggesting it as a promising alternative for oral hygiene maintenance